2021
DOI: 10.15252/embr.202051991
|View full text |Cite
|
Sign up to set email alerts
|

The biochemical basis of mitochondrial dysfunction in Zellweger Spectrum Disorder

Abstract: Peroxisomal biogenesis disorders (PBDs) are genetic disorders of peroxisome biogenesis and metabolism that are characterized by profound developmental and neurological phenotypes. The most severe class of PBDs-Zellweger spectrum disorder (ZSD)-is caused by mutations in peroxin genes that result in both nonfunctional peroxisomes and mitochondrial dysfunction. It is unclear, however, how defective peroxisomes contribute to mitochondrial impairment. In order to understand the molecular basis of this inter-organel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 99 publications
6
51
1
Order By: Relevance
“…Likewise, we cannot rule out that the depletion of some precursors could derive from transcriptional effects. However, we consider this unlikely, as previous transcriptomics studies revealed that solely the absence of peroxisomes does not generally result in global mRNA expression changes [ 57 ].…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, we cannot rule out that the depletion of some precursors could derive from transcriptional effects. However, we consider this unlikely, as previous transcriptomics studies revealed that solely the absence of peroxisomes does not generally result in global mRNA expression changes [ 57 ].…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, we cannot rule out that the depletion of some precursors could derive from transcriptional effects. However, we consider this unlikely since previous transcriptomics studies revealed that solely the absence of peroxisomes does not generally result in global mRNA expression changes [57].…”
Section: Discussionmentioning
confidence: 92%
“…In a recent CP study of peroxisome-deficient cells using peroxins deletion strains of S. cerevisiae as a model system and fibroblasts from a Zellweger syndrome patient, Nübel and co-workers linked accumulation of miss-targeted peroxisomal membrane proteins into mitochondria to metabolic and morphological abnormalities of this organelle ( Nuebel et al, 2021 ). Complexome profiles of yeast strains lacking peroxisomes showed formation of the docking subassembly of the peroxisomal importomer complex in mitochondria, explaining also the incorporation of peroxisomal matrix proteins to this subcellular compartment.…”
Section: Complexome Profiling: Perspectivesmentioning
confidence: 99%